132k views
3 votes
Solve for x: -5x^2+6=0

2 Answers

4 votes

Answer:

x= square root of 6/5

Explanation:

-5x^2+6=0

-5x*2=-6

5x^2=6

5x=square root of 6

x= square root of 6/5

User Serras
by
5.1k points
0 votes

Answer:


(√(30))/(5), -(√(30))/(5)

Explanation:

We have the equation
-5x^2 + 6 = 0

Since we know that any number multiplied by 0 is 0, we can safely make the term
0x to add to this.

So our equation now is
-5x^2 + 0x + 6

We can now solve for this using the quadratic formula, which is
\frac{{ - b \pm \sqrt {b^2 - 4ac} }}{{2a}}}.

b is the coefficient on the x term, a is the coefficient on the
x^2 term, and c is the constant.

Let's substitute inside the equation, since we know
a = -5,
b = 0 and
c = 6.


\frac{{ - 0 \pm \sqrt {0^2 - 4\cdot-5\cdot6} }}{{2\cdot-5}}}\\\\\frac{{ 0 \pm \sqrt {0 -( -120)} }}{{-10}}}\\\\\frac{{ 0 \pm \sqrt {120} }}{{-10}}}\\\\\frac{{\pm \sqrt {120} }}{{-10}}}\\\\


(√(30))/(5), -(√(30))/(5)

Hope this helped!

User Blackdad
by
5.5k points